COMPRESSED AIR ENGINE WITH ACTIVE CONTROL UNDER PRESSURE SATURATION IN THE CONTROL OF OSCILLATING ROTATION - Alves, Alexandre de Castro; Tusset, Angelo Marcelo; Balthazar, Jose Manoel; Rocha, Rodrigo Tumolin; Janzen, Frederic Conrad (Revista Interdisciplinar de Pesquisa em Engenharia, 2019)
This work evaluates the oscillating rotation of a connecting-rod-crank mechanism as compressed air engine with input saturation control. The mechanism positions are controlled with a non-conservative excitement by air pressure that controls the positions of the angular output. It is evaluated the control of the angular position through the command by pneumatic valve controlled by the method of control. Initially applies control without restricting the maximum pressure that achieves saturation pressure in response to the control function. Therefore, must be limited maximum pressure in the input at 1MPa for the application and control in industrial pneumatic equipment. Thus, it is analyzes the parametric error for the angular position relative to the desired control, with and without saturation function. However, when applying the saturation control function checks that the system becomes stable despite the parametric error increase at one decimal place of 10-3 to 10-2. Therefore, the parametric errors obtained are suitable and can be applied to control the angular oscillation of the output to the compressed air engine as a stable system by controlling the saturation.